Advancing and reversing succession as a function of time since fire and insect outbreaks: An 18 year in situ remeasurement of changes in forest composition. (4th January 2021) - Leduc, Albanie; Leduc, Alain; Kneeshaw, Daniel; Maleki, Kobra; Bergeron, Yves
Abstract: Aims: In the boreal mixedwood, fire initiates forest succession; however, over time other disturbances such as insect outbreaks cause pulses of mortality and opportunities for recruitment of shade‐intolerant species. Questions: What are the respective roles of time since fire and insect outbreaks in driving directional, vs cyclical and retrogressive succession? Do assessments from direct measurements and chronosequence approaches converge? We hypothesise that the chronosequence approach will accurately characterise large‐scale compositional patterns especially in younger stands and that direct measurements will better describe small‐scale, non‐directional changes in succession. Location: Boreal mixed wood of northwestern Quebec (79°1′ W, 48°30′ N). Methods: We sampled 469 plots over an 18‐year interval (in 1991 and 2009) in mixed hardwood/conifer forests to observe in situ the changes in stands having originated from seven fires covering a 249‐year chronosequence. Results: The combination of the remeasurement and chronosequence analyses validates predictions of forest succession. Our results indicate that time since last fire is the dominant factor explaining forest succession for the first 150 years after fire and globally at the scale of the entire forest, although smaller‐scale disturbances such as spruce budworm outbreaks can change the course of forest succession, especially at stand scales. Conclusion: While time since fire is the dominant driver of forest succession in younger forests, secondary disturbances, such as spruce budworm outbreaks, can advance or reverse forest succession in older forests. This study also serves as a validation of the overall patterns described in spatial chronosequence approaches at the landscape level in fire‐dominated systems but highlights that local succession may deviate from the overall pattern especially in older forests or in forests affected by non‐stand re‐initiating intermediate disturbances. Abstract : A chronosequence is made up of different spatially distinct forest stands with different time since origin that are considered to approximate a temporal sequence in stand development. Rarely do we have the possibility to verify whether these different stands constitute real temporal relays. This study presents in situ changes of stand composition of different ages (249‐years chronosequence) and evaluates how well these changes approximate chronosequence predictions.